Handbook of paint raw materials - Flick, Ernest W. (Noyes Publications, 1989)
This book describes nearly 4000 raw materials. Data represent selections from manufacturers' descriptions. Contents: Antifoams, Defoamers, Dispersants, Surfactants; Driers and Antiskining Agents; Extenders, Fillers, Pigments; Flame/Fire Retardants; Flatting Agents; Latex Emulsions; Oils; Preservatives, Bactericides, Fungicides; Resins; Rheological/Viscosity Control Agents; Silicone Additives; Titanium Dioxides.
Includes index.
Keywords: Paint materials -- Handbooks, manuals, etc.; elektronické knihy; electronic books